Para-stomal variceal bleed, 9 years post-radical cystectomy: An Unusual emergency at a usually missed location - Suvraraj Das; Gaurav Aggarwal; Sujoy Gupta (Archive of Urological Research - Peertechz Publications, 2020)
Parastomal or stomal varices are infrequently encountered with majority occurring secondary to portal hypertension. They can be a source of considerable morbidity, mandating hospitalization, blood transfusions, angiographic or surgical intervention and may even be fatal. We describe a rare instance of parastomal variceal bleeding in a patient who had undergone a radical cystectomy and ileal conduit-urinary diversion in 2011 for a high-grade muscle-invasive transitional cell carcinoma of the urinary bladder, which was managed via simple suture-ligation. Though reported as a temporary measure, he remained stable till date. The point to note is that this approach is beneficial, especially in an emergent scenario- to avoid missing this unusual occurrence, at a usually missed site.